Dynamic locking plates provide symmetric axial dynamization to stimulate fracture healing. Issue 8 (21st May 2015) - Tsai, Stanley; Fitzpatrick, Daniel C.; Madey, Steven M.; Bottlang, Michael
ABSTRACT Axial dynamization of an osteosynthesis construct can promote fracture healing. This biomechanical study evaluated a novel dynamic locking plate that derives symmetric axial dynamization by elastic suspension of locking holes within the plate. Standard locked and dynamic plating constructs were tested in a diaphyseal bridge‐plating model of the femoral diaphysis to determine the amount and symmetry of interfragmentary motion under axial loading, and to assess construct stiffness under axial loading, torsion, and bending. Subsequently, constructs were loaded until failure to determine construct strength and failure modes. Finally, strength tests were repeated in osteoporotic bone surrogates. One body‐weight axial loading of standard locked constructs produced asymmetric interfragmentary motion that was over three times smaller at the near cortex (0.1 ± 0.01 mm) than at the far cortex (0.32 ± 0.02 mm). Compared to standard locked constructs, dynamic plating constructs enhanced motion by 0.32 mm at the near cortex and by 0.33 mm at the far cortex and yielded a 77% lower axial stiffness (p < 0.001). Dynamic plating constructs were at least as strong as standard locked constructs under all test conditions. In conclusion, dynamic locking plates symmetrically enhance interfragmentary motion, deliver controlled axial dynamization, and are at least comparable in strength to standard locked constructs. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 33:1218–1225, 2015.